Purinergic Signaling and Cochlear Injury-Targeting the Immune System? - Köles, László (Int J Mol Sci, 2019)
Hearing impairment is the most common sensory deficit, affecting more than 400 million people worldwide. Sensorineural hearing losses currently lack any specific or efficient pharmacotherapy largely due to the insufficient knowledge of the pathomechanism. Purinergic signaling plays a substantial role in cochlear (patho)physiology. P2 (ionotropic P2X and the metabotropic P2Y) as well as adenosine receptors expressed on cochlear sensory and non-sensory cells are involved mostly in protective mechanisms of the cochlea. They are implicated in the sensitivity adjustment of the receptor cells by a K(+) shunt and can attenuate the cochlear amplification by modifying cochlear micromechanics. Cochlear blood flow is also regulated by purines. Here, we propose to comprehend this field with the purine-immune interactions in the cochlea. The role of harmful immune mechanisms in sensorineural hearing losses has been emerging in the horizon of cochlear pathologies. In addition to decreasing hearing sensitivity and increasing cochlear blood supply, influencing the immune system can be the additional avenue for pharmacological targeting of purinergic signaling in the cochlea. Elucidating this complexity of purinergic effects on cochlear functions is necessary and it can result in development of new therapeutic approaches in hearing disabilities, especially in the noise-induced ones.